A developmental study of glutamatergic neuron populations in the ventrobasal and the lateral geniculate nucleus of the thalamus: Comparing Genetic Absence Rats from Strasbourg (GAERS) and normal control wistar rats - ONAT, FİLİZ; KİRAZLI, ÖZLEM (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
An imbalance of GABAergic inhibition and glutamatergic excitation is suspected to be the cause of absence epileptic seizures. Absence seizures are known to be generated in thalamocortical circuitry. In the present study we used light microscopy immunohistochemistry to quantify the density of glutamate+ve neurons at two developmental stages (P10 and P60) in two thalamic nuclei, the ventrobasal (VB) and lateral geniculate nucleus (LGN) in Wistar rats and compared the results with similar data obtained from genetic absence epilepsy rats from Strasbourg (GAERS). Rats were perfused transcardially with glutaraldehyde and paraformaldehyde fixative, then samples from VB and LGN were removed from each animal and sectioned. The glutamatergic neurons were labelled using light-microscopic glutamate immunohistochemistry. The disector method was used to quantify the glutamate+ve neurons in VB and LGN of GAERS and Wistar rats. The data were statistically analyzed. The distribution of the glutamate+ve neurons in the VB thalamic nucleus showed a significant reduction in the neuronal profiles per unit thalamic area from P10 to P60 in both Wistar and GAERS. The decrease was greater in the GAERS compared to the Wistar animals. However, in the LGN no reduction was observed either in the Wistar or in the GAERS. Comparing the density of glutamate+ve neurons in the VB thalamic nucleus of P10 of Wistar animals with of P10 GAERS showed statistically significant greater densities of these neurons in GAERS than in the Wistar rats. However no significant difference was present at P60 between the Wistar and GAERS animals. The disproportional decrease in GAERS may be related to the onset of absence seizures or may be related to neurogenesis of absence epilepsy. (C) 2016 ISDN. Published by Elsevier Ltd. All rights reserved.
Keywords: GAMMA-HYDROXYBUTYRATE MODEL; WAVE DISCHARGES; EPILEPSY RATS; ALZHEIMERS-DISEASE; SPONTANEOUS SPIKE; CELL COUNTS; SEIZURES; MECHANISMS; SYSTEM; CORTEX